Genetic and Environmental Influences on Negative Life Events From Late Childhood to Adolescence. Issue 5 (4th February 2013) - Johnson, Daniel P.; Rhee, Soo Hyun; Whisman, Mark A.; Corley, Robin P.; Hewitt, John K.
Abstract : This multiwave longitudinal study tested two quantitative genetic developmental models to examine genetic and environmental influences on exposure to negative dependent and independent life events. Participants ( N  =   457 twin pairs) completed measures of life events annually from ages 9 to 16. The same genetic factors influenced exposure to dependent events across time and increased in magnitude during the transition to adolescence. Independent events were less genetically influenced than dependent events in boys, but not girls. Shared environmental influences decreased in magnitude as youth transitioned into adolescence. Nonshared environmental influences were mostly age specific and contributed significantly to both types of events at all ages. Results provide theoretical implications for developmental risk pathways to stress exposure and stress‐related psychopathology.